Nasionalisme di Tengah Pluralitas dan Kebebasan Pers - Umi Halwati; Imam Alfi; Johar Arifin (KOMUNIKA: Jurnal Dakwah dan Komunikasi, 2018)
Indonesian is a nation born from the spirit of nationalism. The spirit of independence and freedom from colonialism finally resulted in the spirit of unity among tribes, races, religions and groups to form Indonesian nationalism. Having the same feeling of destiny and experience could defeat ethnic, cultural and religious differences so that the formation of Indonesia nation was created. Nationalism can be interpreted as the ability to love the nation and state. Nationalism is a state of awareness or a national spirit. Nationalism is not just an instrument that acts as plurality gluing externally, but also a vessel that affirms a plural Indonesian identity in its various cultural dimensions. The press with the freedom of news/ information publications has a dual role, namely the media as an information filter and as a media of national unity. The media as an information filter mean that the media has the authority to conceptualize social reality. It is this conceptualization process that needs to be reconstructed into potential in building and campaigning for nationalism. Applicatively media people see that social reality is packaged in the framework of strengthening the values of nationalism. Then the mass media as a mediator of national unity has the function of providing insight and education as well as preventive efforts in reducing the potential for intolerance and the development of nationalism values.